Pertumbuhan Dan Produksi Kedelai Varietas Anjasmoro Pada Tanah Salin - Usnawiyah, Usnawiyah; Delvian, Delvian (Agrium, 2012)
Increased soybean production  is  competing with the extension of the  use of agricultural land for  non- agricultural needs. Therefore the future expansion of agricultural land can only use marginal lands such as peatlands, wetlands and tidal lands. This paper discusses the growth and production of soybean varieties Anjasmoro in saline environments. Varieties Anjasmoro have total leaf area and the percentage ratio of the canopy  which  is  not  significantly  different  from  the  other  varieties  tested  except  Kipas  Merah.  In  the production of components, seed weight Anjasmoro 100 seeds varieties including higher and statistically the same as the varieties Kipas Putih dan Kipas Merah